Polynomial spline collocation method for nonlinear two‐dimensional weakly singular integral equations - Pedas, Arvet (Mathematical Modelling and Analysis, 1997)
“Polynomial spline collocation method for nonlinear two‐dimensional weakly singular integral equations”Mathematical Modelling Analysis, 2(1), p. 122-129.First Published Online: 14 Oct 2010